2018
DOI: 10.2174/1874205x01812010001
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Mortality Among Elderly Patients Admitted With Neurological Disorders Was Not Predicted by any Particular Diagnosis in a Tertiary Medical Center

Abstract: Background:Neurological disorders (NDs) are associated with high hospital mortality. We aimed to identify predictors of hospital mortality among elderly inpatients with NDs.Methods:Patients aged ≥60 years admitted to the hospital between January 1, 2009 and December 31, 2010 with acute NDs, chronic NDs as underpinnings of acute clinical disorders, and neurological complications of other diseases were studied. We analyzed demographic data, NDs, and comorbidities as independent predictors of hospital mortality. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Anthropometric characteristics of subjects in this study was similar to the data shown by Bacellar et al [13]. Female was the dominant gender, but with no statistically significance in stroke subjects.…”
Section: Discussionsupporting
confidence: 89%
“…Anthropometric characteristics of subjects in this study was similar to the data shown by Bacellar et al [13]. Female was the dominant gender, but with no statistically significance in stroke subjects.…”
Section: Discussionsupporting
confidence: 89%
“…The Information Technology Department at this hospital (IT-HSR) recorded all admissions during the period of the study. Further information regarding the HSR and the method for capturing patients, including details concerning ND diagnostic assessments, can be found in our previously-published studies of the same population 15,16 . We enrolled elderly inpatients with NDs in this study using the following methods: 1) IT-HSR searches of NDs listed in discharge summaries and 2) IT-HSR identification of registered neurological procedures.…”
Section: Patientsmentioning
confidence: 99%
“…Studies of neurological disorders among elders admitted to a tertiary centre in Salvador found epilepsy in 16% of elderly inpatients, and the majority of them had a long LOS 9,10 . Notwithstanding these facts, reports of elderly inpatients admitted with epileptic seizures in Brazil are scarce 7,11,12,13,14,15,16 . The aim of the present study was to identify independent predictors of long LOS in a cohort of elderly inpatients who were admitted with epileptic seizures or experienced seizures during hospitalization.…”
mentioning
confidence: 99%